Theology of Evolution (II): Karl Schmitz-Moormann (1997) and the Trinitarian Creative Call - García Doncel, Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
We continue the presentation of three sets of valuable insights for elaborating a theology of «creation in evolution» [cf. PENSAMIENTO, vol. 63 (2007), pp. 605-636]. In this article, we focus on the insights, published posthumously in 1997, of the Catholic German biologist and theologian Karl Schmitz-Moormann. Inspired by Teilhard and his metaphysics of union, Schmitz-Moormann introduces his concept of «uni-totality» and observes uni-totalities in the course of the process of evolution beginning from sub-atomic particles to human groups. He observes the diversity of union, explained by nuclear interaction or by interpersonal love. He analogously considers the triune God as the supreme Uni-totality united by love, which created uni-totalities approximate as authentic «trinitarian vestiges». His central insight is to see continuous creative evolution as the response to a «creative call» by the triune Creator who does not force but only invites nothingness (absolute or relative) to approach the richness of its being by joining the next elements in every level. This non-imperative but loving action that allows entire creation to come-to-be reveals to us a Creator that is also realizing himself in a supreme loving union according to a metaphysics of coming-to-be. The progressive creation of information about divine omniscience and freedom also allows a loving response to the invitation of the creative call. We offer here the authentic texts of Schmitz-Moormann, and we also investigate their origin. His insight concerning the «creative call» theologically enriches Karl Rahner’s insight about the transcendental action that sustains «active self-transcendence», which the insight of Denis Edward will later enrich, since he sees «active self-transcendence» as the «Spirit’s own action» within a relational ontology.
Keywords: K. Schmitz-Moormann; Teilhard de Chardin; metaphysics of union; uni-totality; supreme Uni-totality; metaphysics of coming-to-be (gignontology); creative call; trinitarian vestiges; creation of information; creation of freedom